The performance of TBM disc cutter in soft strata: A numerical simulation using the three-dimensional RBD-DEM coupled method. (January 2021) - Fang, Yong; Yao, Zhigang; Xu, Wanghao; Tian, Qingfeng; He, Chuan; Liu, Sijin
Highlights: A new proposed three-dimensional RBD-DEM coupled method. An improved constitutive model for fully weathered granite. The cutting process simulation of disc cutter in soft strata. Investigated the performance of disc cutter in soft strata. Abstract: Though disc cutters are widely used in mixed strata, eccentric wear of disc cutters in soft part of mixed strata is still an important factor influencing the efficiency and cost of TBM tunnelling. The eccentric wear of disc cutters is closely related to their motion state, however, in-depth research on this issue are still less. This paper introduces a three-dimensional RBD-DEM coupled method, adopting a newly developed RBD coupling calculation program in which the mutual interaction between disc cutters and strata was considered. Based on this method, the cutting process of disc cutter was simulated and the performance of disc cutter was investigated. The results show that the slip ratio decreases as the depth of penetration depth increases, however, the degree of influence is not obvious in terms of a critical value of penetration depth, on the contrary, if the penetration depth is too large, the slip ratio fluctuation increases. At the same penetration, linear velocity does not have significant effects on slip ratio, but it can have great effects on the torque of the disc cutter, especially the torque at the start-up phase. Existing eccentric wear would lead to the periodic fluctuations of angular velocity and enlarge both the rolling force and thrust force, therefore, existing wear will accelerate eccentric wear.